Role of unfolded protein response in the apoptosis induced by alphaarterivirus : IRE1α as an essential pathway for In vitro replication - Colina, Santiago Emanuel (2025)
The perturbation of ER homeostasis by viral infection gives rise to the unfolded protein response (UPR), characterized by the activation of three signaling pathways. PERK, IRE1, and ATF6 have been identified as the primary mediators responsible for restoring homeostasis or leading to apoptosis in response to stress. Alphaarterivirus equid, known as equine arteritis virus (EAV), is a RNA virus with importance in the equine industry that could persist in semen and lead to abortions in pregnant mares. The present article explores the consequences of in vitro infection with the EAV Bucyrus strain on UPR. Employing RT-PCR, qPCR and Western blot, our investigation has revealed the activation of PERK and IRE1α pathways, whilst ATF6 has been suppressed. Furthermore, the p38α MAPK, caspase-12, and CHOP genes were found to be upregulated, demonstrating the induction of apoptosis. Finally, in the inhibition experiments, the PERK pathway was found to be implicated in the modulation of viral replication in the initial phases of infection. Conversely, the IRE1α pathway was identified as the predominant UPR pathway in EAV replication, as evidenced by the complete inhibition of replication observed in these experiments. Consequently, the further exploration of this UPR pathway is necessary to determine whether it can effectively suppress EAV replication.